Development new media (feedstock) for biogas production - Mel, Maizirwan (2014)
Feedstock is one of the most challenging parts of building and operating an anaerobic digestion system. Feedstock quantity and quality must be established and longterm contracts. It must be secured early in the project. This is because anaerobic digestion systems must be designed around available feedstock, and not the other way around. There are three types of feedstock that can go into an anaerobic digestion system such as byproducts produced by a farming operation, off-farm source materials, and energy crops. Different feedstock has a different biogas yield and also has own different feeding strategy. Our new media formula was developed and used to produce biogas with high concentration of biomethane and less hydrogen sulpide concentration. This development has been performed in double stages of digestion process. Optimized the organic loading rate (OLR) Hydraulic Retention Time (HRT) have been applied in this project. This biogas composition produced has shown a good performance in engine testing.